Catur purusa artha: Antecedent and moderator for improving business performance - Kusyana, Dewa Nyoman Benni; Hartati, Putu Sri; Sugianingrat, Ida Ayu Widani; Dewi, Ida Ayu Sasmita; Arsha, I Made Risma M. (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
This research was conducted to determine the influence of organizational culture on business performance, mediated by innovation and moderated by catur purusa artha. The subjects of this research were the cooperative heads or managers of 503 cooperative units in Denpasar City. The Yamane formula was used to determine the sample size, which was determined to be 83 cooperative heads/managers using a proportionate random sampling technique. Data analysis was carried out using structural equation modelling – partial least squares (SEM-PLS). Data analysis using PLS was carried out with two measurement models, namely the outer model and the inner model. The results of the analysis prove that organizational culture has no significant effect on business performance. Innovation acts as a full mediating variable in the influence of organizational culture on business performance. Catur purusa artha has a positive and significant effect on business performance and acts as a moderator of the relationship between organizational culture and business performance. The findings of this research answer the shortcomings of the resource-based view by placing innovation, which is a dynamic capability, as a mediator and catur purusa artha as a moderator.